Selected cannabis cultivars modulate glial activation: in vitro and in vivo studies - Sigal Fleisher-Berkovich; Nitzan Sharon; Yvonne Ventura; Valeria Feinshtein; Jonathan Gorelick; Nirit Bernstein; Shimon Ben-Shabat (Journal of Cannabis Research)
Abstract Introduction Multiple sclerosis (MS) is a chronic autoimmune disease of the central nervous system characterized by neuroinflammation, demyelination and axonal loss. Cannabis, an immunomodulating agent, is known for its ability to treat MS effectively. However, due to variations in the profile of secondary metabolites, especially cannabinoids, among cannabis cultivars, the effectiveness of cannabis treatment can vary, with significant variability in the effects on different biological parameters. For screening available cultivars, cellular in vitro as well as pre-clinical in vivo assays, are required to evaluate the effectiveness of the wide range of chemical variability that exists in cannabis cultivars. This study evaluated comparatively three chemically diverse cannabis cultivars, CN2, CN4 and CN6, containing different ratios of phytocannabinoids, for their neuroinflammatory activity in MS model. Materials and methods In vitro experiments were performed with lipopolysaccharide (LPS)-activated BV-2 microglia and primary glial cells to evaluate the effect of different cannabis cultivars on nitric oxide (NO) and inflammatory cytokines, as well as inducible nitric oxide synthase (iNOS) protein expression. An in vivo experiment using the experimental autoimmune encephalomyelitis (EAE) MS model was conducted using Myelin oligodendrocyte glycoprotein (MOG) as the activating peptide. The cannabis extracts of the cultivars CN2, CN4, CN6 or vehicle, were intraperitoneally injected with clinical scores given based on observed symptoms over the course of study. At the end of the experiment, the mice were sacrificed, and splenocyte cytokine secretion was measured using ELISA. Lumbar sections from the spinal cord of treated MS mice were evaluated for microglia, astrocytes and CD4+ cells. Results Extracts of the CN2 cultivar contained tetrahydrocannabinolic acid (THCA) and tetrahydrocannabinol (THC) without cannabidiol (CBD), and a number of monoterpenes. CN4 contained cannabidiolic acid (CBDA) and tetrahydrocannabidiolic acid (THCA), with significant amounts of THC: CBD in a 1:1 ratio, as well as sesquiterpenes and some monoterpenes; and CN6 contained primarily CBDA and THCA, as well as THC and CBD in a 2:1 ratio, with some sesquiterpenes and no monoterpenes. All extracts were not cytotoxic in glial cells up to 50 µg/ml. Dose dependent inhibition of LPS-induced BV2 as well as primary microglial NO secretion confirmed the anti-inflammatory and anti-oxidative activity of the three cannabis cultivars. CN2 but not CN4 reduced both astrocytosis and microglial activation in lumbar sections of EAE mice. In contrast, CN4 but not CN2 significantly decreased the secretion of TNFα and Interferon γ (IFNγ) in primary splenocytes extracted from EAE mice. Conclusions While both cannabis cultivars, CN2 and CN4, significantly reduced the severity of the clinical signs throughout the course of the study, they modulated different inflammatory mediators and pathways, probably due to differences in their phytocannabinoid composition. This demonstrates the differential potential of cannabis cultivars differing in chemotype to regulate neuroinflammation and their potential to treat MS.